ICT Usage in Enterprises in the Years 2010–2019 – Poland in Comparison with Other European Union Countries - Kupis-Fijałkowska, Aleksandra; Misztal, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2023)
As Eurostat’s glossary explains, the term Information and Communication Technologies (ICT): ‘covers all technical means used to handle information and aid communication. This includes both computer and network hardware, as well as their software.’ In both local and global perspective, the ICT impact on modern economies and societies is undeniable. Moreover, it is growing, as the usability and technical capabilities are expanding. The researchers recognised that the ICT expansion in enterprises is a stimulant for economic development, as it strengthens competitiveness and innovation. Its impact on labour markets is significant, and constantly increasing demand for digital competences and ICT specialists can be observed. In both global and local perspective, the ICT sector is growing dynamically along with its value share in GDP. Monitoring the development of ICT usage as well as analysing how it stimulates socio‑economic transformations and growth are crucial for global leaders, governments and local authorities all over the world in order to formulate policy at all levels. Also, it plays a significant role in modern businesses expansion, as it strengthens innovativeness and competitiveness. The main objective of the paper is to study the ICT usage development in Poland against other EU countries from the enterprises’ perspective in the years 2010–2019 (before the COVID–19 pandemic and Brexit). The research presented was based on Eurostat data. The variables were selected on the basis of the literature review on ICT usage, as well as the criterion of data availability and comprehensiveness. The exploratory data analysis methods dealing with three‑way data structures, i.e. the between and within‑class principal component analysis, were used, and the presentation of the results was supported by factorial maps (scatterplots and biplots). In the analysed period, enterprises in all the European Union Member States intensified their ICT usage. Despite the positive trend from 2010 to 2019, Poland remained far behind the leading countries, and more precisely, was in the group of the least developed ones.